Assassination Classroom: Time to Show Off a Hidden Talent - Vol 5 5, Time to show off a hidden talent - Matsui, Yusei, 1981-; Miyaki, Tetsuichiro (San Francisco, California : VIZ Media, LLC, 2015)
"Intramural relations are at an all-time low: Principal Asano wants to crush Koro Senseis 3-E baseball team while Koro Sensei wants to avenge Principal Asanos sabotage of 3-Es midterms. Then the government sends in a new Special Forces operative--a ruthless father figure who tests Karasumas combat coaching skills. Youll never guess which student does him proud! And when Koro Sensei digs a swimming pool to help his students cool off, they discover a new weakness of his--as well as how cute their classmates look in swimsuits!"--Publisher description.
"Rated T+ for older teen"--Page 4 of cover.
aTranslated from the Japanese.
Keywords: Junior high school students -- Comic books, strips, etc; Assassination -- Comic books, strips, etc; Extraterrestrial beings -- Comic books, strips, etc; Teacher-student relationships -- Comic books, strips, etc; Graphic novels -- Japan; Translations into English; Science fiction comics; Graphic novels; Comics (Graphic works)